Integrasi Konseling Kelompok Cognitive Behavior Therapy dengan Passive Music Therapy untuk Mereduksi Academic Anxiety, Efektifkah? - Situmorang, Dominikus David Biondi; Mulawarman, Mulawarman; Wibowo, Mungin Eddy (Jurnal Kajian Bimbingan dan Konseling, 2018)
The aim of this study is to determine the effectiveness of group counseling with cognitive behavior therapy approach using passive music therapy technique to reduce the academic anxiety of students who is writing thesis. The research used quasi-experimental design (pretest, posttest, and follow-up). Group counseling was conducted for five meetings, and follow-up was performed two weeks after the treatment. Research subjects were seven students. Purposive sampling technique was used to select the subjects, that is based on inclusion criteria and level of academic anxiety which is obtained from academic anxiety scale (rxy = 0.536-0.823, coefficient alpha = 0.963). The results showed that group counseling with cognitive behavior therapy approach using passive music therapy technique was significantly effective to reduce the students’ academic anxiety in pretest vs. posttest and pretest vs follow-up, but in posttest vs. follow-up there was a slight increase in academic anxiety. Passive music therapy which is integrated into group counseling with cognitive behavior counseling approach, it is not only able to solve the individual problems but also able to help individuals to analyze their thoughts and behaviors through passive music activities with guided imagery.